An Italian Adaptation of the Brief Resilient Coping Scale (BRCS) and Attitudes During the Covid-19 Outbreak - Murphy, Mike; Lami, Andrea; Moret-Tatay, Carmen (Frontiers in Psychology, 2021)
Resilience has attracted the interest of the scientific community during the Covid-19 outbreak, as a protective factor in mental health. As the migrant population arguably has one of the most vulnerable profiles in the current health crisis, the aim of this study is to assess the psychometric properties of the Italian version of the Brief Resilient Coping Scale (BRCS) across native and migrant residents in Italy, and to compare scores across these two populations. Other personal attitudes to the current restrictions were considered. Preliminary psychometrics were tested in a version of the translated instrument with an independent sample. A second independent sample was used to analyse the differences between migrant and native adults. The results showed no differences between the new version and the previous Spanish adaptation or the original instrument. Moreover, no differences were found between the migrant and non-migrant group. BRCS scores were predicted by attitudes toward Covid-19 but not by migrant or native group. These results suggest that the BRCS may be a useful tool to measure resilience in Italy at time of pandemic, irrespective of cultural differences.